Pelaksanaan Kearifan Lokal di Kawasan Wisata Pulau Pahawang, Kabupaten Pesawaran, Propinsi Lampung - Zainab Ompu Jainah; Lintje Anna Marpaung (Universitas Bandar Lampung (UBL), 2017)
Pahawang Island is one area that has great tourism potential in Pesawaran District, Lampung Province which offers the beauty of a bay with a variety of marine biota and mangrove forests. The abundance of this potential is not supported by an adequate regulation of the development of tourist areas based on local wisdom that regulates local wisdom that exist in the community in relation to the conservation of natural resources in the framework of the development of tourist areas. The problem in this research is how the implementation of local wisdom in the community Tourism Area Pahawang Island, Pesawaran District, Lampung Province? Problem approach is done by normative and empirical juridical method by using primary data and secondary data and also qualitative data analysis. Based on the results of research can be concluded that the local wisdom that occurred on the island of Pahawang be one example of success in saving mangrove forest in Lampung. Pahawang Island Village has Village Regulation (Perdes) Mangrove Rescue which contains about the prohibition and sanction for villagers and migrants who cut down mangrove trees. The Perdes was made citizens not solely because of the success of the NGO's environmental campaign, but because of local wisdom that reappeared.